Clinical significance of neutrophil-to-lymphocyte ratio as a predictor of lymph node metastasis in gastric cancer - Toshiyuki Kosuga; Tomoki Konishi; Takeshi Kubota; Katsutoshi Shoda; Hirotaka Konishi; Atsushi Shiozaki; Kazuma Okamoto; Hitoshi Fujiwara; Michihiro Kudou; Tomohiro Arita; Ryo Morimura; Yasutoshi Murayama; et al. (BMC Cancer, 2019)
Abstract Background Precise staging is indispensable to select the appropriate treatment strategy for gastric cancer (GC); however, the diagnostic accuracy of conventional modalities needs to be improved. This study investigated the clinical significance of the preoperative neutrophil-to-lymphocyte ratio (NLR) for the prediction of pathological lymph node metastasis (pN+) in GC. Methods This was a retrospective study of 429 patients with GC who underwent curative gastrectomy. The predictive ability of NLR for pN+ was examined in comparison with that of computed tomography. Results The preoperative NLR ranged from 0.6 to 10.8 (median, 2.0), and the optimal cut-off value for predicting pN+ was 1.6 according to the receiver operating characteristic curve with the maximal Youden index. Multivariate analysis identified a NLR ≥ 1.6 (odds ratio (OR) 3.171; 95% confidence interval (CI) 1.448–7.235, p = 0.004) and cN+ (OR 2.426; 95% CI 1.221–4.958, p = 0.011) to be independent factors associated with pN+ in advanced GC (cT2-T4). On the other hand, a NLR ≥ 1.6 was not useful for predicting pN+ in early GC (cT1). In advanced GC, a NLR ≥ 1.6 detected pN+ with a higher sensitivity (84.9%) and negative predictive value (NPV) (63.9%) than conventional modalities (50.0 and 51.7%, respectively). When the subjects were limited to those with advanced GC with cN0, the sensitivity and NPV of a NLR ≥ 1.6 for pN+ increased further (90.7 and 81.0%, respectively). Conclusion The preoperative NLR may be a useful complementary diagnostic tool for predicting pN+ in advanced GC because of its higher sensitivity and NPV than conventional modalities.